Risk factors of type 2 diabetes mellitus of outpatients in the community health centres of South Denpasar Subdistrict - Sri Trisnawati; I Ketut Tangking Widarsa; Ketut Suastika (Public Health and Preventive Medicine Archive, 2013)
The prevalence of Diabetes Mellitus (DM) is increasing throughout the world particularly type 2 DM. The changes in people’s lifestyle and diets are assumed to play major roles. This study aimed to examine the relationships between the risk factors such as obesity based on body mass index (BMI) and waist circumference (WC), hypertension, inactivity, smoking, and age ≥50 years with the incidence of type 2 DM. A matched case-control design involving of 136 pairs of men with family history of diabetes was used in this study. Cases and controls were selected from outpatients at the South Denpasar Sub-District Public Health Center. Data from outpatients were collected by interviewing, physical and laboratory examinations. Data were analyzed using McNemar and logistic regression. Based on the statistical analysis the Odds Ratio (OR) of the factors such as obesity (based on waist circumference) was 5.2 [95%CI: 2.31-11.68] with p=0.001 and age ≥50 years was 4 [95%CI: 1.74-9.21] with p=0.001. It can be concluded that patients with obesity (based on waist circumference) and age of ≥50 years have a higher risk for type 2 DM. It suggested that the occurrence obesity in the community can be reduced by modifying the lifestyle and eating patterns of the community.